Food texture experiences across nine age groups in Indian infants from urban areas - Devezeaux de Lavergne, Marine; Thielecke, Frank; Antille, Nicolas; Fries, Lisa R.; Ross, Carolyn F.; Smith-Simpson, Sarah (Frontiers in Nutrition, 2024)
The introduction of complementary food plays a fundamental role for dietary behaviours later in life. Little is known on influences of age on food textures acceptance in young Indian children. Thus, the objective of this cross-sectional study was to describe the relationship between age and food texture experiences in young children aged 4-36 months in India from urban areas using a parental reported survey. This surveystudy relies on aA face-to-face parent survey, which was conducted comprising 306 children arranged categorised into nine age groups. Questions focused on food texture experience considering 16 textures were analysed. Textures such as dissolvable, sticky, and soupy/liquidy were already accepted by more than half of 4-5 month-old infants. In India, soupy/liquidy is a more common base texture than pureed. Indeed, pureed was found to be introduced to a majority of infants only from 8-9 months onwards. Food textures such as rubbery, slippery, and foods with skin were more likely rejected in the youngest children. With increasing age, the refusal probability of food textures decreased. Our survey showed food texture experiences in Indian children aged from 4-36 months. It provides useful insights for parents and health care professionals by contributing to the understanding of texture acceptance during the transition to complementary foods.